Pengertian, Teori dan Tipe Kepemimpinan - Ansori; Hadiyanto Zulbasri; Ardaini; Kasful Anwar (Jurnal Riset Multidisiplin Edukasi, 2025)
Leadership is a key element in the success of organizations, both in the public and private sectors. This article aims to comprehensively examine the definition, theories, and various types of leadership that have developed within the fields of management and organizational behavior. The discussion begins with a fundamental understanding of leadership as a process of influencing individuals or groups to achieve common goals. It then explores various leadership theories, including trait theory, behavioral theory, contingency theory, as well as transformational and transactional leadership. Each theory offers different approaches and focuses in explaining what makes a leader effective. The article also reviews several leadership types such as authoritarian, democratic, laissez-faire, charismatic, participative, and adaptive leadership—each with its own strengths and challenges depending on organizational context and member characteristics. This study is expected to serve as a reference for practitioners, academics, and policymakers in understanding the dynamics of effective leadership in the modern era.